2006
DOI: 10.1088/0957-4484/17/18/013
|View full text |Cite
|
Sign up to set email alerts
|

Selective growth of silica nanowires in silicon catalysed by Pt thin film

Abstract: Selective growth of amorphous silica nanowires on a silicon wafer deposited with Pt thin film is reported. The mechanism of nanowire growth has been established to follow the vapour liquid solid (VLS) model via the PtSi phase acting as the catalyst. Nanowires grow with diameters ranging from 50 to 500 nm. These bottom-up grown nanowires exhibit photoluminescence with a stable emission of blue light at 430 nm under excitation. The effect of varying the seed layer thickness (Pt film) from 2 to 100 nm has been st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 19 publications
2
52
0
1
Order By: Relevance
“…(1) The Si nanowires may be firstly nucleated on the catalysts after Si diffuses into the catalyst. And then the residual oxygen in the tube furnace reacts with the Si nanowire and oxides to create a SiO x shell until Si nanowire's complete oxidation [42,43]. (2) The diffused Si atoms on the substrate react with the residual oxygen in the tube furnace to form SiO x as the sources.…”
Section: Resultsmentioning
confidence: 99%
“…(1) The Si nanowires may be firstly nucleated on the catalysts after Si diffuses into the catalyst. And then the residual oxygen in the tube furnace reacts with the Si nanowire and oxides to create a SiO x shell until Si nanowire's complete oxidation [42,43]. (2) The diffused Si atoms on the substrate react with the residual oxygen in the tube furnace to form SiO x as the sources.…”
Section: Resultsmentioning
confidence: 99%
“…They found that the growth of a-Si nanowires was controlled by a solid-liquid-solid (SLS) mechanism, in which the only possible Si source came from the Si substrate and Si nanowires grow from the Si x Ni eutectic liquid droplets. Similarly, the growth of SiO x nanowires on Si was reported using a Pd/Au thin film [28], a Pt thin film [29], and a Co thin film as catalysts [30], in which the Si source was Si substrate. In these cases, the tips of the nanowires are supposed to comprise metal silicide particles, playing a catalytic role.…”
Section: Resultsmentioning
confidence: 86%
“…A metastable Pt 2 Si 3 phase was also reported. Besides the complexity of phases and the growth kinetics, Fe-and Pt-silicides are considered to be very important in the electronic industry for making Ohmic contacts, and are also used as a catalyst for the growth of various nano-structures [37,38]. Fig.…”
Section: Resultsmentioning
confidence: 99%